Correlations study between the selenium content of wheat grass (Triticum aestivum L.) and wheat seeds grown on different soil types - Tamás, Melinda; Márton, Melinda; Mészáros, Sándor; Lányi, Szabolcs; Csapó, János (Acta Agraria Debreceniensis, 2010)
In the course of the research we determined selenium and dry-matter content of 35 wheat grasses and 35 wheat seeds. The selenium content of the preparation plant samples was measured by spectrofluorimetric determination (ʎexcitation=380 nm, ʎemission=519 nm) of the resulted piaz-selenol complex. It was established that between the selenium content of the wheat grass and wheat seed the correlation coefficient was 0.36 at p=0.05 level which indicates a medium close correlation. Similarly, there was a medium close correlation between selenium content of the wheat grass calculated on dry-matter basis and total selenium content of the wheat, with a correlation coefficient of 0.40 at p=0.02 level.